Автоколебательная система на основе объемных резонаторов, подобных неустойчивым бильярдам Синая и Бунимовича - Еременко, З. Е.; Ганапольский, Е.М. (Видавничий дім "Академперіодика" НАН України, 2007)
For the first time, the idea to use quasioptical stochastic microwave resonators similar to the threedimensional unstable Bunimovich and Sinai billiards as the oscillating systems of microwave generators is proposed and implemented. The spectral properties of such resonators in the eightmillimeter wave band are studied. The most important of them is the effect of the repulsion of spectral lines. It leads to the complete removal of the spectrum degeneration. As a result, the dense spectrum is formed where the spectral lines are splitted and have a high quality factor. A self-oscillating system based on stochastic resonators is designed. A Gunn diode was used as an active element in this system. We detected and studied the electromagnetic monofrequency generation in active stochastic resonators in the millimeter wave band.